Experiments and Analysis of a Nonlinear Sickle‐Shaped Cantilever Beam Piezoelectric Energy Harvester for Wind Energy Harvesting. Issue 23 (17th October 2022) - Yu, Gang; He, Lipeng; Wang, Shuangjian; Tian, Xiaochao; Zheng, Xiaotian; Cheng, Guangming
Abstract : Achieving broadband energy harvesting at low frequencies is a difficult area of research today. To solve the aforementioned problems, herein, a nonlinear sickle‐shaped cantilever beam piezoelectric energy harvester (S‐PEH) for wind energy harvesting is proposed. It has a high‐voltage output in the wind speed range of 5.37–18.23 m s −1 . The S‐PEH is consists of a collector and a transducer. The collector converts wind energy into rotating mechanical energy and excites the transducer by means of magnetic coupling, thus realizing the conversion of mechanical energy to electrical energy. The special structure of the transducer's sickle‐shaped cantilever beam type can effectively harvest wind energy in low‐frequency environment and broaden the range of harvesting wind speed in high voltage. The structure and principle of S‐PEH are analyzed by theory and simulation and are experimentally verified. The results show that when the magnet on the rotor is 15 mm away from the magnet of the piezoelectric sheet, the transducer angle is 90°, the load resistance is 100 kΩ, the voltage of the blower is kept at 120 V, and the system has a maximum power of 563 μW. Moreover, it can successfully make low‐power electronics work. Abstract : Herein, a nonlinear sickle‐shaped cantilever beam piezoelectric energy harvester for wind energy harvesting is proposed. It has a high‐voltage output in the wind speed range of 5.37–18.23 m s −1 . In addition, it can successfully operate low‐power electronic devices, such as scientific calculators and light‐emitting diodes.